EFFECTIVE STATEGIES FOR COMBATING RELIGIOUS AND VIOLENT EXTRIMISM IN KENYA - Doreen Nyamosi (IJRDO - Journal of Social Science and Humanities Research, 2019)
Religious extremism has been an issue of concern to global peace in the recent past. Various countries have set up strategies to deal with this issue .Kenya on its part has been grappling with religious and violent extremism through establishment of a number of measures to curb terrorism. Despite the various efforts, religious extremism has been an elusive issue even with massive investment in dealing with this vice